Inhibition of ferric salts on phosphorus-accumulating organisms in simultaneous chemical precipitation for phosphorus removal - Xiao, Anqi; Yu, Jianbo; Lin, Ziyuan; Cao, Meng; Jian, Shuai; Lin, Shuxuan; Zhou, Jian (Frontiers in Microbiology, 2025)
To comply with the increasingly strict phosphorus (P) effluent standard, ferric salts are commonly used as a simultaneous precipitant to supplement the biological P removal process. However, ferric residue from the chemical process can be carried by the return sludge into the biological system, potentially affecting the biological P removal process. This study demonstrated that ferric salts had significant inhibitory effects on the biological P removal process. The activity and relative abundance of phosphate-accumulating organisms (PAOs) decreased after adding ferric salts. P uptake rate dropped from 10.31 to 2.39 mg/(g SS⋅h) and the relative abundance of PAOs decreased from 2.51% to 0.21% when ferric salts increased from 0 to 42 mg Fe3+/L. P release and uptake by PAOs were inhibited, and bioavailable P and poly-P in the sludge dropped after ferric addition. As a result, the chemical P removal with ferric precipitation contributed more to P removal, and the ortho-P in the sludge spiked. The inhibition of the biological P removal process may make it difficult to control simultaneous ferric dosing, where the biological P removal process is required to make a major contribution to P removal.